Discipline, surveillance and libidinal pulsion at school: La mirada invisible (2010) - De Taboada Amat y León, Javier (2021)
This article analyzes the film La mirada invisible (2010), directed by Diego Lerman, based on the novel Ciencias Morales by Martín Kohan.The film focuses on the surveillance work of a preceptor of the Colegio Nacional de Buenos Aires during the dictatorship of El Proceso. Weconsider that the microcosm represented in the film operates as a metonym for the disciplinary society that Argentina had become during the dictatorship, exposing how the repressive structure permeates all social institutions, particularly the school. The protagonist of the film, however, in her dedication to exercising the task of surveillance and control, also discovers the libidinal space of the pulsion. Finally, we will also explore the construction of the space represented in the film, with monumentality and verticality as its main features.